PERAN RELATIONSHIP MARKETING DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS NASABAH - Hidayah, Ria Nurul; Rahayu, Yayuk Sri (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This research aims to determine whether there is an influence of Sharia marketing and relationship marketing characteristics on customer loyalty at Bank NTB KCP Kediri with satisfaction as an intervening variable. This research was conducted on Bank NTB KCP Kediri customers with a total of 8852 customers. This type of research is quantitative with the path analysis research method and the analytical technique used is SPSS version 25. The number of samples used is the Slovin formula with a margin of error that has been set at 10% so a total of 99 respondents are needed. To collect research data by distributing questionnaires and purposive random sampling. The results of hypothesis testing show that Sharia marketing characteristics do not directly influence loyalty and satisfaction, while relationship marketing directly influences loyalty and satisfaction. The results of hypothesis testing indirectly show that the characteristics of Sharia marketing and relationship marketing through satisfaction do not have a significant influence on customer loyalty. So the influence of Sharia marketing and relationship marketing characteristics on customer loyalty at Bank NTB KCP Kediri with satisfaction as an intervening variable is rejected.